2016
DOI: 10.3390/en9050330
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Windup Load Frequency Controller Design for Multi-Area Power System with Generation Rate Constraint

Abstract: Abstract:To deal with the problem of generation rate constraint (GRC) during load frequency control (LFC) design for a multi-area interconnected power system, this paper proposes an anti-windup controller design method. Firstly, an H ∞ dynamic controller is designed to obtain robust performance of the closed-loop control system in the absence of the GRC. Then, an anti-windup compensator (AWC) is formulated to restrict the magnitude and rate of the control input (namely power increment) in the prescribed ranges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…This limit agrees with recent EU-wide targets, which expect to have an interconnection power of 10% in the year 2020 [46]. Most contributions found in the literature review either do not limit the maximum tie-line power, or it is not indicated [81][82][83][84].…”
Section: Supply-side Modelingsupporting
confidence: 85%
“…This limit agrees with recent EU-wide targets, which expect to have an interconnection power of 10% in the year 2020 [46]. Most contributions found in the literature review either do not limit the maximum tie-line power, or it is not indicated [81][82][83][84].…”
Section: Supply-side Modelingsupporting
confidence: 85%
“…Although this control loop has been extensively analyzed in the past [1][2][3], it is still an area of active research [4-12, ?-12, ?-12, ?-12], mainly because the control design objectives are now revisited from a different, more complex, perspective. Deregulation, distributed generation and microgrids, renewable energy sources, coupled to security issues in power systems seen as cyber-physical systems [5-8, 10, 12, 13], lead to the increasing need and interest for intelligent distributed control [4,[14][15][16], while accounting for saturation induced instabilities [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Reference [18] presents an H ∞ Load Frequency Controller Design for Multi-Area Power System enhanced with an Anti-Windup scheme that handles Generation Rate Constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Various controlling methodologies and strategies of load frequency control (LFC) of single and interconnected EPSs have been extensively reported in the literature which can be classified into: (i) conventional and classical controllers, (ii) artificial intelligence controllers, (iii) meta-heuristic based-on controllers, (iv) hybridisation of these methods, and (v) recently, model predictive based on controllers. Among classical controllers, H-∞ based loop-shaping method [5,6], sliding mode based controllers [7][8][9], and fuzzy logic based control strategies [10][11][12] are employed for solving LFC problem of interconnected EPSs. It is worth mentioning that these aforesaid controllers have few shortcomings such as: designer experience is essential, longer computational time, and complex design procedures.…”
Section: Introductionmentioning
confidence: 99%